Innovative Strategies for Addressing Diverse Learning Needs in Ghanaian English Language Classrooms - Agbevivi, Shine Lillian Gifty (ELE Reviews: English Language Education Reviews, 2024)
The complexity of contemporary classrooms in Ghana necessitates innovative strategies to address diverse learning needs effectively. Hence, addressing the latter in English language classrooms (ELCs) is critical. This study explored the understanding of English language teachers regarding differentiated instruction and how they addressed the varied needs and abilities of learners in primary schools in Ho Municipality. The study is grounded in the Differentiated Instruction (DI) Theory and utilized a sample of 12 teachers from four primary schools selected through convenience sampling. Data collection involved semi-structured interviews and classroom observations, which were meticulously coded and analyzed thematically to uncover patterns and themes. The study revealed that teachers view differentiated instruction as essential for accommodating diverse learning styles/approaches/dispositions, adapting teaching techniques to individual needs, and promoting inclusive practices. Again, it revealed that primary school English language teachers employed flexible grouping, diverse assessments, action-oriented teaching, technology integration, individualized explanations, and student-centered and peer learning activities. However, the consistent use of tiered assignments to address varying academic levels was notably absent, indicating a gap in the full implementation of DI. The study concludes that employing various innovative teaching strategies in ELCs is crucial for enhancing primary school educational quality and student achievement.